2002
DOI: 10.1046/j.1365-2362.2002.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying in myotonic dystrophy

Abstract: Patients with MD suffering from nausea, vomiting and early satiety, displayed a slow gastric emptying. Treatment with erythromycin had only moderate effect on gastric emptying or gastric symptoms, but reduced diarrhoea in a majority of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Researchers highlight that up to 40% of children and young adults can experience GI symptoms, which include pain, bloating, altered bowel habit, and constipation. 9 Furthermore, Rönnblom et al 10 conducted a study in 2002 to monitor gastric emptying in 10 patients with MD; in this study, they suggested that MD is associated with reduced gastric motility. However, because of a lack of high-quality studies, it is still up for debate whether MD causes CIPO via damage to the enteric nervous system, smooth muscle, or secondary endocrine changes.…”
Section: Figurementioning
confidence: 99%
“…Researchers highlight that up to 40% of children and young adults can experience GI symptoms, which include pain, bloating, altered bowel habit, and constipation. 9 Furthermore, Rönnblom et al 10 conducted a study in 2002 to monitor gastric emptying in 10 patients with MD; in this study, they suggested that MD is associated with reduced gastric motility. However, because of a lack of high-quality studies, it is still up for debate whether MD causes CIPO via damage to the enteric nervous system, smooth muscle, or secondary endocrine changes.…”
Section: Figurementioning
confidence: 99%
“…In 28% of patients, gastrointestinal problems occurred before the diagnosis of DM1 was made and 25% of patients find the worst symptoms are gastrointestinal related. The burden for patients of gastrointestinal related symptoms has generally been underecognised 47 48…”
Section: Myotonic Dystrophy Typementioning
confidence: 99%
“…91,92 Of these, abdominal pain, dysphagia, vomiting, diarrhea, coughing while eating, and fecal incontinence were the most common in one survey 92 ; up to 25% of patients consider gastrointestinal involvement as the most disabling feature of their disease. 93 Delayed gastric emptying and gastroparesis have indeed been well documented, [94][95][96] and instances of gastric volvulus described. 97 In Duchenne dystrophy, gastric motor dysfunction is an early feature, 98 resulting in hypomotility and gastroparesis, 99 which can be profound and result in acute gastroparesis and gastric dilatation.…”
Section: Muscle Diseasementioning
confidence: 98%